2015
DOI: 10.1155/2015/145140
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Long-Term Memory following Chronic Administration ofEryngium planumRoot Extract in Scopolamine Model: Behavioral and Molecular Study

Abstract: Eryngium planum L. (EP) is as a rare medicinal plant with a lot of potentials as pharmaceutical crops. The aim of our study was to assess the effect of subchronic (28-fold) administration of a 70% ethanol extract of EP roots (200 mg/kg, p.o.) on behavioral and cognitive responses in Wistar rats linked with acetylcholinesterase (AChE), butyrylcholinesterase (BuChE), and beta-secretase (BACE-1) mRNA levels and AChE and BuChE activities in the hippocampus and frontal cortex. On the last day of experiment, 30 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 55 publications
1
8
0
1
Order By: Relevance
“…− ) was found in the MS/MS spectrum of compound 64 and corresponded with the tetrahydroxyflavone moiety.Several triterpenoid saponins were found in the samples. Similar to Ożarowski et al[17], we observed precursors and the fragmentation pattern as in the related species, E. planum. The pseudo-molecular ion at m/z 471.34903 corresponded with the molecular formula C 30 H 47 O 4 E. planum and E. maritimum[22].…”
supporting
confidence: 90%
“…− ) was found in the MS/MS spectrum of compound 64 and corresponded with the tetrahydroxyflavone moiety.Several triterpenoid saponins were found in the samples. Similar to Ożarowski et al[17], we observed precursors and the fragmentation pattern as in the related species, E. planum. The pseudo-molecular ion at m/z 471.34903 corresponded with the molecular formula C 30 H 47 O 4 E. planum and E. maritimum[22].…”
supporting
confidence: 90%
“…[ 24 27 , 43 – 45 ]. A large scale of evidence has pointed out to multiple pharmacological effects of the genus Eryngium species including antioxidant, anti-inflammatory, antihemolytic, antinociceptive effects, and protective agent against neurodegenerative deseases [ 25 , 28 , 48 – 50 ]. For instance, Eryngium planum , which is a rare medicinal plant, was studied to determine the effect of subchronic administration of a 70 % ethanol root extract (200 mg/kg, p.o.)…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the experiment, after the last dose of the Eryngium extract, scopolamine (SC) was administered intraperitoneally to a group of animals (treated). In the animals treated with the Eryngium extract, an improvement in long-term memory produced by the EP extract in both scopolamine treated and control group was registered with decreased mRNA AChE, BuChE, and BACE-1 levels, especially in the frontal cortex, suggesting the potential efficacy of this extract in this kind of pathologies [ 25 , 28 , 48 – 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although sometimes a lack of correlation between the results at the formation of the protein and transcriptional occurs and reflects the complex interaction at the level of transcription and translation of particular substance of natural origin ( Ożarowski et al, 2013 , 2015 ; Mikołajczak et al, 2015 ), clearly establish the profile of anti-inflammatory OAO-ASA (8) and the mechanisms responsible for this is not possible on the basis of the obtained results.…”
Section: Discussionmentioning
confidence: 90%